Input bias current reduction technique for operational amplifier in a standard CMOS technology. Issue 7 (16th May 2020) - Chin, Koken; Ohsawa, Mamoru; Kitajima, Atsushi; Arai, Yoshiaki; Yamashita, Jun; Ito, Hisashi; San, Hao
Abstract: This paper presents input bias current ( Ibias ) reduction technique for high impedance CMOS op‐amps with the proposed current compensation circuit to deal with the leakage current caused by Electro‐Static Discharge (ESD) protection circuit of the IC. High input impedance CMOS op‐amps are widely used for the application of high precision sensors with quite small input current. However, the leakage current of ESD protection circuit for op‐amp causes a nonideality error of the Ibias . Especially, the ESD leakage current increases drastically at the high temperature environment, and hence the Ibias of CMOS op‐amp also increased significantly. An ESD leakage current compensation circuit is introduced to reduce the Ibias of CMOS op‐amp. The prototype amplifier with the proposed current compensation circuit is designed and fabricated in standard 0.7 µm CMOS technology. Measurement results show that the Ibias is reduced to a 100 pA or less from a typical 2.3 nA at 150°C.